Long Head of the Biceps Tendon Tenotomy versus Subpectoral Tenodesis in Rotator Cuff Repair - Kim, Jangwoo (Clin Orthop Surg, 2020)
BACKGROUD: Lesions of the long head of the biceps tendon (LHBT) are one of the most common pathologies in patients with a rotator cuff tear. Although various procedures have been shown to be effective for treating LHBT lesions during rotator cuff repair, no consensus has been reached regarding the most effective treatment. The purpose of this study was to compare the outcomes of tenotomy vs subpectoral tenodesis of the LHBT in arthroscopic rotator cuff repair. METHODS: The records of 135 patients who underwent arthroscopic rotator cuff repair with biceps tenotomy or subpectoral tenodesis for a partial LHBT tear of > 50% were initially reviewed. Finally, 77 patients (38 patients with tenotomy and 39 patients with subpectoral tenodesis) with an intact rotator cuff, who underwent a functional evaluation at 1 year postoperatively, were enrolled in this retrospective study. RESULTS: The average follow-up was 13.3 ± 4.36 months (13.2 ± 1.4 months in the tenotomy group and 13.6 ± 2.7 months in the subpectoral tenodesis group; p = 0.416). Demographic and surgical data were not significantly different between the 2 groups. Preoperatively, biceps groove tenderness, Speed's test, and Yergason test results were positive in 27.3%, 27.3%, and 10.4% of the study subjects, respectively. Compared with preoperative values, all functional scores including shoulder muscle power were significantly improved postoperatively, and no significant intergroup difference was observed (all p > 0.05). A visible Popeye deformity was not encountered in either group at the final follow-up. Eight patients in the tenotomy group and 7 patients in the subpectoral tenodesis group complained of mild anterior shoulder pain (p = 0.731), and 4 patients in each group complained of groove tenderness (p = 0.969). No surgical or postoperative complication occurred in either group. CONCLUSIONS: Both biceps tenotomy and subpectoral tenodesis performed during rotator cuff repair improved pain and function and resulted in comparable clinical outcomes. Residual symptoms associated with the remnant LHBT in the groove may not be a problem after adhesion of LHBT.